The distribution of competitive research grants from the National Institute for Food and Agriculture: A comparison of 1862 land grant universities, 1890 land grant universities, and other institutions - Wilson, Norbert L. W.; Reynolds, Kenesha; Wade, Tara; Walters, Lurleen M. (Applied Economic Perspectives and Policy, 2024)
This article evaluates the U.S. Department of Agriculture, National Institute for Food and Agriculture (NIFA) competitive grant funding awarded to predominately White 1862 land grant institutions (LGUs), historically Black 1890 LGUs, and non-land grant institutions. We present the historical distribution of funding for agricultural research. Much of the inquiry centers on the differential funding of the 1862 LGUs, 1890 LGUs, and non-land grant institutions. We discuss the implications for academic and community stakeholders. Results show that, on average, 1890 LGUs and non-land grant institutions receive less competitive grant funding than 1862 LGUs for the same award programs. We show that the disparity falls from 2010 to 2019.
Keywords: Land Grant Universities; Food and Agriculture; Grants